Fuzzy Image Processing, Analysis and Visualization Methods for Hydro-Dams and Hydro-Sites Surveillance and Monitoring - Mihaela, Gordan; Ovidiu, Dancea; Mihaela, Cislariu; Ioan, Stoian; Aurel, Vlaicu (IntechOpen, 2012)
None